Occupant health in buildings: Impact of the COVID-19 pandemic on the opinions of building professionals and implications on research. (January 2022) - Awada, Mohamad; Becerik-Gerber, Burçin; White, Elizabeth; Hoque, Simi; O'Neill, Zheng; Pedrielli, Giulia; Wen, Jin; Wu, Teresa
Abstract: The objectives of this study are to investigate building professionals' experience, awareness, and interest in occupant health in buildings, and to assess the impact of the COVID-19 pandemic on their opinions, as well as to compare the research on occupant health in buildings to professionals' opinions. To address these objectives, a mixed research methodology, including a thorough review of the literature (NL  = 190) and an online survey (NS  = 274), was utilized. In general, there is an increasing research interest in occupant health and a heightened interest in health-related projects, among professionals, following the COVID-19 pandemic. Specifically, among the nine different building attributes examined, indoor air quality was the most researched building attribute with a focus on occupant health and was also presumed to be the most important by the professionals. Professionals considered fatigue and musculoskeletal pain to be the most important physical well-being issues, and stress, anxiety, and depression to be the most important mental well-being issues that need to be the focus of design, construction, and operation of buildings to support and promote occupant health, while eye-related symptoms and loss of concentration were the most researched physical and mental well-being symptoms in the literature, respectively. Finally, professionals indicated that COVID-19 pandemic had significant effect on their perspectives regarding buildings' impact on occupant health and they believed future building design, construction and operation will focus more on occupant health because of the pandemic experience. Highlights: There is an increasing research interest in healthy buildings. IAQ is the most researched building attribute and most important to professionals. Most researched and important health issues in buildings are presented. The COVID-19 pandemic impacted professionals' opinions regarding healthy buildings. Challenges and opportunities regarding healthy buildings movement are provided.